2002
DOI: 10.1139/y02-081
|View full text |Cite
|
Sign up to set email alerts
|

Functional and autoradiographic characterization of dopamine D2-like receptors in the guinea pig heart

Abstract: Dopamine receptors include the D1- (D1 and D5 subtypes) and D2-like (D2, D3, and D4 subtypes) families. D1-like receptors are positively and D2-like receptors negatively coupled to the adenylyl cyclase. Dopamine D2-like (D4 subtype) receptors have been identified in human and rat hearts. However the presence of D2 and D3 receptor subtypes is unclear. Furthermore, their role in cardiac functions is unknown. By autoradiographic studies of guinea pig hearts, we identified D3 and D4 receptors, using the selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Then dopamine has predominantly role in the control of cardiac function since it is regulating the sympathetic tone throughout regulating the release of norepinephrine from terminal sympathetic nerves. In addition others studies have been demonstrated the expression of dopamine receptors in mammal hearts [40][41][42]. Also mRNA levels for D 1 , and D 4 receptors have been reported in mammals heart including human heart [43,44].…”
Section: Discussionmentioning
confidence: 88%
“…Then dopamine has predominantly role in the control of cardiac function since it is regulating the sympathetic tone throughout regulating the release of norepinephrine from terminal sympathetic nerves. In addition others studies have been demonstrated the expression of dopamine receptors in mammal hearts [40][41][42]. Also mRNA levels for D 1 , and D 4 receptors have been reported in mammals heart including human heart [43,44].…”
Section: Discussionmentioning
confidence: 88%
“…Cardiovascular effects of DAs are thought to be related to the activation of dopaminergic and non-dopaminergic receptors [17,18]. D1-like and D2-like dopamine receptors located at various sites within the vascular, cardiac and renal regions have been shown to mediate cardiovascular and renal effects [19]. The different subtypes of α2-receptors regulate the norepinephrine and noradrenaline release in sympathetic neurons [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Monassier et al (2007) showed that haloperidol blocks human recombinant hERG potassium channels in COS-7 monkey kidney cells via stimulation of sigma 2 receptors. On the other hand, haloperidol has affinity for dopamine D 2 receptors, which are located in guinea pig heart (Gomez et al 2002). Dopamine D 2 agonists may increase QT interval duration (Gomez et al 2002).…”
Section: Fig 2 Changes Of Qtc In Isolated Heartsmentioning
confidence: 99%
“…On the other hand, haloperidol has affinity for dopamine D 2 receptors, which are located in guinea pig heart (Gomez et al 2002). Dopamine D 2 agonists may increase QT interval duration (Gomez et al 2002). However, haloperidol acts as a dopamine D 2 antagonist and the dopaminergic effect on the heart rate and QT interval duration is disputable.…”
Section: Fig 2 Changes Of Qtc In Isolated Heartsmentioning
confidence: 99%